A neo-sumerian clay nail of Gudea in the collection of the Department of Ancient Studies of Stellenbosch University - Van Dijk-Coombes, Renate Marian (2016)
Fil: Van Dijk-Coombes, Renate Marian. Stellenbosch University; Sudáfrica